'Agite, agite et uenite!' Corrupted breath, corrupted speech and encounters with the restless dead in Geoffrey of Burton's Vita sancte Moduenne virginis. Issue 2 (15th March 2022) - Gordon, Stephen
ABSTRACT: Written accounts of supernatural encounters often include reference to speech acts performed by the evil agent. In such instances, the human interlocutor may be overcome by sickness, sometimes leading to death. Despite the close relationship that existed between physical and metaphysical health in theological discourse, encounters with 'diseased' supernatural agents generated little in the way of overt explanatory frameworks, especially in historical or literary writings. Focusing on the tale of the Drakelow revenants found in Geoffrey of Burton's Vita sancte Moduenne virginis ( c .1118–35), this article evaluates the aetiology of interactions between the living and the undead, with particular reference to the dangerous speech exhibited by the restless ghost. The investigation begins with an exploration of the medical and theological context behind the belief in the transmission of ill health, before concluding with an examination of how such motifs were utilised for didactic effect in the creation of Geoffrey's Vita .